Ratified but Resisted: Refugees, the Right to Asylum in International Law, and Western State Practice - Mahmuluddin; Zulkarnain (CV Global Research Publication, 2025)
The refugee problem has become one of the most pressing global challenges in contemporary international relations. Armed conflict, persecution, insecurity, and humanitarian crises have compelled millions to flee their countries of origin in search of safety and survival. In response, the international community, under the auspices of the United Nations, has established a legal framework for refugee protection, most notably through the 1951 Refugee Convention, its 1967 Protocol, and the institutional role of the United Nations High Commissioner for Refugees (UNHCR). Despite widespread ratification of international refugee law, implementation varies significantly among states. Many Western countries, while formally committed to international instruments, increasingly adopt restrictive asylum policies and practices such as narrow interpretations of refugee status, procedural barriers, externalization of responsibilities, and securitized approaches to protection. This study uses a qualitative doctrinal and analytical legal approach. It relies on secondary sources including international legal instruments, UNHCR documents, and peer-reviewed literature. The analysis reveals a growing gap between legal commitments and state behavior. Western asylum governance demonstrates selective and minimalist compliance with international refugee law, reflecting restrictive interpretations and practices that undermine the spirit of asylum protection. Contemporary refugee governance in the West does not represent a wholesale rejection of international law but rather a pattern of limited compliance that weakens the normative foundations of asylum rights.